Pentingnya Kolaborasi: Guru sebagai Agen Kunci dalam Meningkatkan Penerimaan Peserta Didik Baru - Gunawan, Lucia Sincu; Narimo, Narimo; Yuniati, Rosita (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Digital marketing is overwhelmly replacing offline marketing. One of the classic challenges faced by private schools is student enrollment. The purpose of the programm is to increase teacher’s participation in new student admissions (PPDB) through marketing strategy sessions, teacher motivation class, and a workshop on creating audiovisual media using mobile phones. The community service was held on January 2nd, 2024, and was attended by 34 participants, including principals, teachers, and education staffs from SMK PMB Kutoarjo, SMP PMB Pituruh, and SMP PMB 1 Kutoarjo. The questionnaire data was analyzed descriptively. The training results indicated that most teachers (94.1%) were willing to participate in PPDB digital marketing by sharing promotional media (65.6%), creating promotional media (59.4%), making videos (50%), and involving students in media creation (31.3%) and sharing media (43.8%). Efforts to enhance the participation of teachers in PPDB require personal commitment as well as the support of leaders and policy stakeholders. Collaborative efforts involving teachers as key agent include peer teacher, students, and alumni.